Pelatihan Pembuatan Media Asesmen Digital Berbasis Gamifikasi bagi Kelompok Guru di Kabupaten Majene: Pelatihan Pembuatan Media Asesmen Digital Berbasis Gamifikasi bagi Kelompok Guru di Kabupaten Majene - Saparuddin Saparuddin; Firdaus Daud; Intan Marzuki; Annisa Paramaswary Aslam; Andi Citra Pratiwi (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
The use of digital technology in learning has positive potential to increase the effectiveness and efficiency of the learning process, including for evaluation purposes. The use of digital technology in learning in Indonesia has increased since the Covid-19 pandemic. However, the use of gamification-based digital technology is still limited, especially in Majene Regency, West Sulawesi Province. The use of gamification in learning can have a positive influence on creating an interesting and enjoyable learning atmosphere for students, thereby increasing interest and motivation to learn. In connection with this, this activity was carried out as an effort to increase the knowledge of teachers in Majene Regency regarding four types of gamification-based digital assessment media, namely Quizizz, Kahoot, Blooket, and Quizlet. This activity is carried out through three main stages, namely (a) presentation of material, (b) practice, and (c) discussion. The results of the training showed an increase in participants' knowledge regarding the four types of gamification-based digital assessment media that had been trained.